Muscle or nothing! Where is the excess protein going in men with high protein intakes engaged in strength training? - Reidy, P. T. (The Journal of Nutrition, 2020)
The amount and optimal timing of protein consumption for maintaining and maximizing muscle mass has been heavily investigated and is often controversial (1). Special emphasis has been placed on the particular impact of postexercise protein consumption on maximizing skeletal muscle growth (1, 2). Skeletal muscle biopsy studies have made some progress in determining interactions between the dose, type, and composition of supplemental protein on these outcomes (1). Although these muscle biopsy studies are well-equipped to infer muscle-specific responses, they have some inherent limitations (1). Limitations aside, these studies are invaluable in pioneering the muscle-specific responses, and have dominated the field for the past 2 decades (1).